2018
DOI: 10.1007/s13197-017-3002-0
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional quality of different grades of adult male chinese mitten crab, Eriocheir sinensis

Abstract: This study mainly investigated the composition of adult male Chinese mitten crab () from four grades/sizes (Grade I: 200-249 g; Grade II: 175-199 g; Grade III: 150-174 g; Grade IV: ≤ 150 g). The results showed that the grade III crabs had the largest gonadsomatic index (GSI), which was significantly higher than the grade I and grade II crabs, no significant difference was found with the grade IV crab. Significant differences in moisture and total lipid contents were observed among various edible parts from dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
43
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 25 publications
(35 reference statements)
8
43
1
Order By: Relevance
“…This may be attributed to the higher protein content of precocious crabs, which has been showed in table . Gly and Ala contribute sweet flavours, whereas Glu acid contributes a strong umami taste (Wang et al, ). Hence, the higher contents of these in precocious crabs may enhance the flavour of precocious crabs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be attributed to the higher protein content of precocious crabs, which has been showed in table . Gly and Ala contribute sweet flavours, whereas Glu acid contributes a strong umami taste (Wang et al, ). Hence, the higher contents of these in precocious crabs may enhance the flavour of precocious crabs.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the levels of various functional dietary substances have been determined (Sun et al, ; Wu et al, ), including highly unsaturated fatty acid, phospholipids, and Cu contents, and the comparisons were previously made between other species of crabs and between those from different places of origin (Jiang et al, ; Wang et al, ). Whereas the nutritional qualities of different grades of adult male Chinese mitten crab were determined in a recent study (Wang et al, ), studies of precocious crabs are mainly focused on factors that lead to precocity. To date, the precocity of Chinese mitten crabs has been linked to the genetic (Li, Hou, & Wei, ; Li, Kang, Zhao, Wen, & Han, ) and nutritional (Cheng & Wang, ; He, Yin, & Zhu, ) factors, to cultivation conditions such as high temperature (Xu, Zhang, & Shen, ; Zhang & Xu, ), and to imbalances of dietary lipids (Lu et al, ; Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although there was no significant difference in HSI between female and male crabs, the GSI of female crabs was higher than male crabs, it could explain that gonad of female E. sinensis reached sexual maturity on November and needed to take enough energy (Wang et al, ; Ying, Yang, & Zhang, ). HSI of female crabs in D4 was the highest, and at the same significant level with D3 and D5.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we can conclude that the dietary replacement of FO/VO had predominant influence on the aroma profiles of gonad, followed by hepatopancreas. In addition, the results showed that the effects of dietary replacement on female crabs was greater than male crabs, this may be due to the fast ovarian maturation of female crabs in the late of fattening period (Chang et al, ; Wang et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation